Multisensory reading promotion in academic libraries - Yu, Wenyan; Jiang, Yiping; Wu, Yanqi; Cheng, Yanxia (Frontiers in Psychology, 2023)
To confront college students’ new reading patterns and the continuous decline in academic library borrowing rates, we conducted empirical research on promoting multisensory reading as a way to attract students’ attention, and to stimulate interest in, and promote the practice of, reading through a library program called “Reading Today Listening Everyday” (RTLE) on a library’s WeChat public account. The program involved 48 librarians and 105 students who were recruited into different groups to co-create, edit and release multisensory tweets every workday. Multisensory contents including text-based content, audio-based content and emotional resonance were presented to evoke readers’ visual, audio, and emotional senses to induce more reading practice. Using the Context, Input, Process and Product (CIPP) evaluation method, the multisensory presentation in RTLE program was proven to be effective in promoting library reading with a high number of tweeted page views and an increased borrowing rate for recommended books. In 2020, 269 issues accompanied by 269 audio frequencies garnered 80,268 page views, depending on the caliber of the reading promoter out of the 48 librarians and 52 student anchors behind it. The 484 RTLE-recommended books were borrowed 113 times in 2020, which was a rate 1.46 times higher than in 2019 (77 times). The analysis of the relationship between tweet views and borrowing rates for recommended books indicates that more page views indicate greater reader interest, leading to increased borrowing. From readers’ feedback and comments, the gain afforded by multisensory reading can improve higher-level reading trends such as the number of reading interests, enjoyment, engagement, etc.